Role of diffusion weighted magnetic resonance imaging of intra and extra axial intracranial lesions - Chakra, V. Vishwas; Singh, Dalpat; Makwana, Mohan; Chouhan, A. L.; Lal, Kanwar (International Surgery Journal, 2017)
Background: Diffusion weighted imaging (DWI) has a wide range of applications in the evaluation of intracranial pathological conditions. It provides a specific diagnosis in few situations, and adds to the information provided by conventional sequence in many others. Methods: The present study was conducted in the Department of Radiology, Dr. S. N. Medical College, Jodhpur, Rajasthan. Participants after understanding the study protocol and procedure, were asked to give their written consent for the study. Results: In the study group of 115 patients (41%) were females and (59%) males. Infarcts comprised 45.2% of the total cases out of these acute infarcts constituted 30 cases (57.7%); 18 (34.6%) chronic infarcts and 4 (7.6%) were subacute infarcts. All cases of acute infarcts and 50% of subacute infarcts showed diffusion restriction. None of the chronic infarcts showed true restriction of diffusion. Among intra axial tumours true restriction was noted in 6 cases. 40% of glioblastoma multiforme showed true diffusion restriction. None of the low-grade gliomas or anaplastic astrocytomas showed diffusion restriction. 75% of medulloblastomas and 50% of lymphomas showed diffusion restriction. All cases of intracerebral abscesses showed true diffusion restriction. The cystic or necrotic component of none of the brain tumours included in this study showed diffusion restriction. All cases of arachnoid cysts seen in this study had low signal on DWI. 33% of meningiomas showed restricted diffusion in this study likely reflecting their high cellularity. All cases of HII showed true diffusion restriction. 25% of these cases showed no signal change on T2WI. Also, the extent of abnormality was noted to be more on DWI than on T2WI. Two cases of extradural empyema seen in this study showed restricted diffusion similar to abscesses. Hypertensive encephalopathy and demyelination did not show restricted diffusion reflecting absence of cytotoxic oedema in these conditions. Conclusions: DW MRI helps in differentiating and characterizing intracranial lesions.